Deforming arthropathy in Thai patients with systemic lupus erythematosus - Lhakum P. (2017)
Copyright © 2016 Wolters Kluwer Health, Inc. All rights reserved. Objective: The aim of this study was to determine the prevalence, spectrum, and clinical, radiological, and serologic findings as well as hand functions among Thai systemic lupus erythematosus (SLE) patients with deforming arthropathy. Methods: All SLE patients attending the rheumatology clinic between January and December 2012 were interviewed, with their complete history and a physical examination being taken. Those with hand deformities were invited to join the study. Results: Forty (8.7%) of 458 SLE patients had deforming arthropathy, with 13 (2.8%) of them having erosive arthritis (EA group) and 27 nonerosive arthropathy (NEA group) (8 [1.8%] with Jaccoud arthropathy [JA subgroup] and 19 [4.1%] with mild deforming arthropathy [MDA subgroup] ). Three of 13 EA patients (0.7% of all SLE patients) had high titer of rheumatoid factor (RF) and anti-cyclic citrullinated peptide (CCP) antibodies that might represent true overlapping between rheumatoid arthritis and SLE. There were no statistically significant differences in autoantibodies, RF, or anti-CCP between the EA and NEA groups or the JA and MDA subgroups, except for discoid rash that was seen more commonly in the MDA subgroup. Rheumatoid factor and anti-CCP were not present in the JA subgroup. Hand joint destruction and deformities were seenmore commonly in the EA group and JA subgroup. The hand grip and palmar pinch strength decreased moderately, with hand functions quite well preserved in all groups. Conclusions: Deforming arthropathy was not uncommon in Thai SLE patients, but true overlapping between rheumatoid arthritis and SLE was rare. Despite significant hand joint deformities and moderately decreased hand grip and palmar pinch strength, preservation of hand functions was generally apparent.